Public administration in the field of administrative services - Лавренова, Ольга Ігорівна; Лавренова, О. І.; Лавренова, Ольга Игоревна; Lavrenova, Olha I. (Riga : Izdevniecība “Baltija Publishing”, 2020)
The article is devoted to the study of public administration in the field of administrative services in Ukraine. It is established that improving the provision of administrative services today is one of the key areas of reform processes in Ukraine, and the formation of effective mechanisms for providing quality administrative services is one of the priorities of public administration. The need to improve the current legislation in the field of administrative services, revision of procedural standards for their provision, as well as the introduction of information and telecommunications technologies in the provision of administrative services determines the relevance of the study of this issue. The concepts and features of administrative services are considered. It is determined that a necessary condition for improving the efficiency of public administration in the field of administrative services is to assess the quality of administrative services, which should be based on the following criteria: availability, efficiency, timeliness, convenience, openness, minimum (fair) cost of administrative services and affordability, professionalism, respect for the person and equality. Problems in the provision of administrative services in Ukraine are studied, among which are the following: shortcomings in legal regulation, complexity and irregularity of the procedure for providing administrative services, lack of standards for providing administrative services, lack of uniform criteria for assessing the quality of administrative services. It is determined that the issues of developing a mechanism for introducing information and telecommunication technologies into the provision of administrative services are becoming especially relevant today. The main directions of public administration in the field of administrative services that need improvement are highlighted.

Стаття присвячена дослідженню державного управління у сфері надання адміністративних послуг в Україні. Встановлено, що покращення надання адміністративних послуг на сьогодні є одним із ключових напрямів реформаторських процесів в Україні, а формування дієвих механізмів надання якісних адміністративних послуг є одним із пріоритетів державного управління. Необхідність удосконалення чинного законодавства у сфері надання адміністративних послуг, перегляду процесуальних норм їх надання, а також впровадження інформаційно-телекомунікаційних технологій при наданні адміністративних послуг визначає актуальність дослідження даного питання. Розглянуто поняття та особливості адміністративних послуг. Визначено, що необхідною умовою підвищення ефективності державного управління у сфері надання адміністративних послуг є оцінка якості адміністративних послуг, яка має базуватися на таких критеріях: доступність, оперативність, своєчасність, зручність, відкритість, мінімум ( справедлива) вартість адміністративних послуг та доступність, професіоналізм, повага до особи та рівність. Досліджено проблеми надання адміністративних послуг в Україні, серед яких: недоліки правового регулювання, складність та нерегулярність процедури надання адміністративних послуг, відсутність стандартів надання адміністративних послуг, відсутність єдиних критеріїв оцінки якості. адміністративних послуг. Визначено, що питання розробки механізму впровадження інформаційно-телекомунікаційних технологій у надання адміністративних послуг сьогодні набувають особливої ​​актуальності. Висвітлено основні напрями державного управління у сфері надання адміністративних послуг, які потребують удосконалення.
Lavrenova O. I. Public administration in the field of administrative services / O. I. Lavrenova // Public administration under modern conditions: concept, features, challenges : Collective monograph. - Riga : Izdevniecība “Baltija Publishing”, 2020. - P. 161-175.
Keywords: public administration; administrative services; information and telecommunication technologies; державне управління; адміністративні послуги; інформаційно-телекомунікаційні технології; Research Subject Categories::LAW/JURISPRUDENCE::Public law